Calabaza, calabaza - Titherington, Jeanne (New York : Scholastic, 1993)
Jamie plants a pumpkin seed and, after watching it grow, carves it, and saves some seeds to plant in the spring.
Translation of: Pumpkin, pumpkin.
Keywords: Pumpkin -- Juvenile fiction; Gardening -- Juvenile fiction; Fiction